Implementasi Model SIUUL dalam Mengembangkan Kemampuan Mengajar dengan PowerPoint - Adinda Naia Ramadhanti; Gealsy Ghefira Tsalsabila; Jihan Aulia Nurjanah; Nabila Hertina Putri; Nur Aryaningsih; Sri Watini (FKIP, Universitas Palangka Raya, 2025)
The implementation of the SIUUL (Simak – Ucap – Ulang) model represents an innovative learning approach to enhance teaching capabilities, especially with the assistance of PowerPoint as a instructual tool. Grounded in the philosophy of human essence and Islamic values, the SIUUL model emphasizes the stages of listening, speaking, and repeating. Effective teacing skills encompass grammar and intonation, priotizing the instructor’s focus. The use of PowerPoint in the teaching method can enhance effectiveness, interactivity, and efficiency in the learning prosess. The research methodology employed is Descriptive Qualitative, focusing on teaching behavior and audience responses. The results indicate that the SIUUL model PowerPoint can collaborate to improve and develop teaching abilities, wherein PowerPoint aids intructors in facilitating learning activities, including non-teaching staff researchers in delivering content more easily.